2020
DOI: 10.1097/aog.0000000000004212
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Mental Health Outcomes Among Women With Early Pregnancy Loss

Abstract: The risk for major depression is common 30 days after treatment for early pregnancy loss, especially among Black women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…In particular, fewer RPL patients were identified as Hispanic or Latino compared with Control patients (UCSF: 11.7% vs 16.6%, Stanford: 16.4% vs 29.3%). Future studies could further examine these differences, with the goal of identifying interventions to reduce any disparities in pregnancy loss risk and clinical care 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fewer RPL patients were identified as Hispanic or Latino compared with Control patients (UCSF: 11.7% vs 16.6%, Stanford: 16.4% vs 29.3%). Future studies could further examine these differences, with the goal of identifying interventions to reduce any disparities in pregnancy loss risk and clinical care 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Research suggest that race can also affect mental consequences (14). Black-women who undergo treatment After an spontaneous abortion are approximately depression that non-Black women.…”
Section: Early and Late Pregnancy Lossmentioning
confidence: 99%
“…Black-women who undergo treatment After an spontaneous abortion are approximately depression that non-Black women. Some of the protective factors that have been cited in the prevention of depression, anxiety and perinatal grief are high standard of education (11, 15), non-immigrant women (14), good conjugal relations (11, 16), and satisfaction with healthcare received (11,16).…”
Section: Early and Late Pregnancy Lossmentioning
confidence: 99%
“…In cohort and population based studies, intense perinatal grief reactions were shown to contribute to detrimental sequelae that included hypertension, weight gain, diabetes, heart problems, substance abuse, and increased risk of suicide ( Dingle et al, 2008 ; Hvidtjørn et al, 2016 ; Lega et al, 2020 ). Overall, there is a paucity of research exploring the mental health concerns and related morbidity for women of childbearing age in primary healthcare settings, particularly in situations where racial or socioeconomic disparities are present ( Marcus et al, 2003 ; Kim et al, 2010 ; Bowen et al, 2012 ; O’Hara and Wisner, 2014 ; Kingston et al, 2015 ; Shorter et al, 2021 ). Studies have recommended a standardized protocol for assessing the emotional well-being of women subsequent to reproductive loss by the primary provider(s) with follow-up visits or phone calls for several months after the loss occurred ( Nynas et al, 2015 ; Farren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%